Integration of Islamic Inheritance and Customary Inheritance: A Study of the Mandailing Community in Tanjung Village - Dinda Suciana Rambe; Naslim Naslim (AT-TAFAHUM: Journal of Law, 2019)
Inheritance law is a part of civil law in Indonesia that regulates the transfer of rights and ownership of property from a deceased person to heirs entitled to receive it. Inheritance law plays an important role because death creates legal consequences regarding the distribution of assets left by the deceased. However, inheritance disputes frequently occur in society, particularly concerning inheritance distribution patterns and the determination of heirs’ rights. In Indonesia, inheritance distribution is regulated not only by the Compilation of Islamic Law but also by customary inheritance systems based on ethnic traditions and local cultural values, which often lead to differences in implementation. This study aims to analyze inheritance distribution practices and examine the interaction between Islamic inheritance law and ethnic customary law in resolving inheritance disputes. The research employs an empirical juridical method with a sociological approach to understand legal practices within society. Data were collected through observations and analysis of social phenomena related to inheritance disputes. The findings indicate that inheritance distribution is influenced by legal awareness, religious values, customary traditions, and family agreements. The coexistence of Islamic inheritance law and customary inheritance law reflects the dynamic nature of inheritance regulation in Indonesia. Therefore, harmonization between legal norms, religious principles, and customary values is necessary to minimize inheritance disputes and promote justice among heirs. This study is expected to contribute to the development of inheritance law and provide references for resolving inheritance disputes within Indonesia’s plural legal system.